Mitochondrial changes in β0-thalassemia/Hb E disease - Kornpat Khungwanmaythawee (2018)
© 2016 Khungwanmaythawee et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. The compound β°-thalassemia/Hb E hemoglobinopathy is characterized by an unusually large range of presentation from essentially asymptomatic to a severe transfusion dependent state. While a number of factors are known that moderate presentation, these factors do not account for the full spectrum of presentation. Mitochondria are subcellular organelles that are pivotal in a number of cellular processes including oxidative phosphorylation and apoptosis. A mitochondrial protein enriched proteome was determined and validated from erythroblasts from normal controls and β°-thalassemia/Hb E patients of different severities. Mitochondria were evaluated through the use of mitotracker staining, analysis of relative mitochondrial genome number and evaluation of mitochondrial gene expression in addition to assay of overall cellular redox status through the use of alamarBlue assays. Fifty differentially regulated mitochondrial proteins were identified. Mitotracker staining revealed significant differences in staining between normal control erythroblasts and those from β°-thalassemia/Hb E patients. Differences in relative mitochondria number and gene expression were seen primarily in day 10 cells. Significant differences were seen in redox status as evaluated by alamarBlue staining in newly isolated CD34+ cells. Mitochondria mediate oxidative phosphorylation and apoptosis, both of which are known to be dysregulated in differentiating erythrocytes from β°-thalassemia/Hb E patients. The evidence presented here suggest that there are inherent differences in these cells as early as the erythroid progenitor cell stage, and that maximum deficit is seen coincident with high levels of globin gene expression.